Family Function and Self-Management of Patients With Early Chronic Kidney Disease: The Mediating Roles of Self-Perceived Burden and Ego Depletion - Cui Y; Liu N; Guo Z; Liu Q; Zhang M; Li J; Mu H; Zhang Y; Chen X (Patient Preference and Adherence)
Yi Cui,1 Na Liu,1 Zhihua Guo,2 Qin Liu,1 Man Zhang,3 Jiayao Li,1 Hezi Mu,4 Yinling Zhang,1,* Xia Chen5,* 1Department of Nursing, Air Force Medical University, Xi’an, People’s Republic of China; 2Department of Military Medical Psychology, Air Force Medical University, Xi’an, People’s Republic of China; 3Department of Nursing, Shaanxi Provincial People’s Hospital, Xi’an, People’s Republic of China; 4Department of Orthopedics, The Second Affiliated Hospital of Air Force Medical University, Xi’an, People’s Republic of China; 5Department of Nursing, Peking University Shenzhen Hospital, Shenzhen, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yinling Zhang, Department of Nursing, Air Force Medical University, Xi’an, 710000, People’s Republic of China, Email zyl-ylz@163.com Xia Chen, Department of Nursing, Peking University Shenzhen Hospital, Shenzhen, 518036, People’s Republic of China, Email 1328219974@qq.comBackground: Effective self-management in the early stage of chronic kidney disease (CKD) is key to delaying disease progression. However, no studies have confirmed that the combined support of internal individual factors and external family environmental factors may play an important role in the self-management of patients with early CKD.Purpose: This current study aims to explore the effect of family function on the self-management of patients with early CKD and examine the mediating roles of self-perceived burden and ego depletion.Patients and Methods: Three hundred and sixty patients with stage 1– 3 CKD participated in the cross-sectional survey and completed structured questionnaires, including the family APGAR index, self-perceived burden scale, self-regulatory fatigue scale and chronic kidney disease self-management instrument. Mplus 8.3 was used to establish a structural equation model.Results: Family function had a positive predictive effect on self-management (β = 0.231, P < 0.001). Self-perceived burden and ego depletion were not only single mediating variables between family function and self-management but also played a chain-mediating role. The total indirect effect was 0.304 (95% CI: 0.234 to 0.388, P < 0.001), accounting for 56.82% of the total effect (β = 0.535, 95% CI: 0.420 to 0.651, P < 0.001).Conclusion: This study highlights the importance of self-management for patients and their families and provides new important theoretical guidance for multiple interventions of improving family function, reducing self-perceived burden and ego depletion to improve self-management, which is of great value in delaying the progression of renal disease.Keywords: chronic kidney disease, family function, self-management, self-perceived burden, ego depletion